Organization of Experience: Examining Inaba Minoru’s Budo as a Form of Art - Edinborough, Campbell C. (Revista de Artes Marciales Asiáticas, 2012)
This article examines how Japanese budo (martial arts), specifically the approach developed by Inaba Minoru (former headmaster of the Shiseikan Budojo, Tokyo), can be functionally understood as a form of art. Through referring to the aesthetic theories of Dennis Dutton, Ellen Dissanayake, and Joseph Carroll, the article examines budo as a means of organizing experience, recognizable alongside painting, dance, theater, and literature.